Relationship between Target Time above Minimum Inhibitory Concentration Achievement Rate of Meropenem Using Monte Carlo Simulation and In-Hospital Survival in Patients with Pseudomonas aeruginosa Bacteremia - Hajime Nakashima; Motoyasu Miyazaki; Tsuneo Kuwamura; Kazutaka Oda; Yumi Haga; Osamu Imakyure (MDPI AG, 2024)
Pseudomonas aeruginosa bacteremia is associated with a high mortality rate, and meropenem (MEPM) is commonly used to treat it. However, the relationship between the time above the minimum inhibitory concentration (fT>MIC) of MEPM and its therapeutic efficacy in P. aeruginosa bacteremia has not been explored. This study aimed to investigate this relationship by defining the target % fT>MIC of MEPM as 75%. The retrospective study spanned 14 years and included hospitalized patients treated with MEPM for P. aeruginosa bacteremia. Monte Carlo simulation was used to calculate the probability of target attainment (PTA) for each patient, and the threshold for a PTA of 75% fT>MIC associated with in-hospital survival was determined using receiver operating characteristic (ROC) curves. The ROC curve-derived PTA associated with improved in-hospital survival was 65.0%, a significant finding in multivariate logistic regression analysis adjusted for patient background factors (odds ratio: 20.49, 95% confidence interval: 3.02-245.23, p = 0.005). This result suggests a dosing regimen that achieves a PTA of at least 65% when the target fT>MIC of MEPM for treating P. aeruginosa bacteremia is defined as 75%.